FOSTERING EARLY LITERACY: EFFECTIVE STRATEGIES FOR TEACHING WRITING TO YOUNG LEARNERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores effective methods for teaching basic writing skills to pre-school and primary school students. Emphasizing the importance of early writing as a foundational literacy skill, the research outlines key developmental stages, addresses common challenges, and proposes innovative teaching techniques. A practical component conducted in Tashkent validates the theoretical insights, highlighting how creative, collaborative, and home-supported strategies enhance young children's writing motivation and competence.